2005
DOI: 10.1007/s00705-005-0573-2
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and recombination analysis of coronavirus HKU1, a novel coronavirus from patients with pneumonia

Abstract: Phylogenetic trees constructed using predicted amino acid sequences of putative proteins of coronavirus HKU1 (CoV-HKU1) revealed that CoV-HKU1 formed a distinct branch among group 2 coronaviruses. Of the 14 trees from p65 to nsp10, nine showed that CoV-HKU1 was clustered with murine hepatitis virus. From nsp11, the topologies of the trees changed dramatically. For the eight trees from nsp11 to N, seven showed that the CoV-HKU1 branch was the first branch. The codon usage patterns of CoV-HKU1 differed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 24 publications
2
45
1
1
Order By: Relevance
“…In addition, there are at least 3 genotypes with recombination between the different genotypes (11,12). Multiple-alignment comparison with other group II coronavirus spike proteins demonstrated that the HCoV-HKU1 spike displays strong similarities to a class I virus fusion protein with a potential cleavage site between residues 760 and 761, which may be processed by a membrane bound, calcium-dependent resident Golgi protease such as furin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are at least 3 genotypes with recombination between the different genotypes (11,12). Multiple-alignment comparison with other group II coronavirus spike proteins demonstrated that the HCoV-HKU1 spike displays strong similarities to a class I virus fusion protein with a potential cleavage site between residues 760 and 761, which may be processed by a membrane bound, calcium-dependent resident Golgi protease such as furin.…”
Section: Introductionmentioning
confidence: 99%
“…Recombination events have been observed for different genotypes of HKU1, in which recombination breakpoints were found on genotypes B and C in the nsp6-nsp7 and nsp16-HE genes, respectively [70] (Figure 4). HKU1 was also shown to be able to recombine with other animal beta-CoVs, such as MHV, at the nsp3, nsp4, nsp6, nsp7, nps9, and nsp10 genes [77] (Figure 4). [78].…”
Section: Genetic Recombination In Human Coronavirusesmentioning
confidence: 99%
“…Although the majority of these infections are selflimited and mild, severe infections can occur mainly in young children, elderly, immunosupressed individuals, and patients with underlying diseases. Influenza (Flu) A and B viruses, respiratory syncytial virus (RSV), parainfluenzaviruses (PIV), adenovirus (ADV), rhinovirus (RhV), enterovirus (EV), and human coronavirus (CoV) OC43 and 229E are classical respiratory pathogens associated with ARI (Atmar et al, 2012;Creer et al, 2006;Dimopoulos et al, 2012;Henderson et al, 1979;Jennings et al, 2008;Ruuskanen et al, 2011;Yun et al, 1995) as well as other currently described viruses such as human metapneumovirus (hMPV) (Van den Hoogen et al, 2004), SARS-CoV (Ksiazek et al, 2003), CoV NL63 ( Van der Hoek et al, 2004) and HKU1 (Woo et al, 2005), MERS-CoV (Zaki et al, 2012), human bocavirus (BoV) (Allander et al, 2005), and others (Ruuskanen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%